Quality of Life among University Students with Premenstrual Syndrome - Victor,Fernanda Figueira (2019)
Abstract Objective To evaluate the quality of life among university students with premenstrual syndrome (PMS). Methods The cross-sectional study was conducted at the Faculdade Pernambucana de Saúde, in Recife, Brazil, between August 2016 and July 2017. Sociodemographic, gynecological, and lifestyle variables, and PMS occurrence, were investigated among 642 students. The short form of the World Health Organization Quality of Life (WHOQOL Bref) questionnaire was used to evaluate four domains of the quality of life of the students: physical, mental, social relationships, and environmental. The American College of Obstetricians and Gynecologists’ criteria were used to define PMS. Results Of the 642 students, 49.9% had PMS, 23.3% had mild PMS and 26.6% had premenstrual dysphoric disorder (PMDD). Most of the students were between 18 and 24 years old, had regular menstrual cycles, and practiced physical activity. Regarding the physical and mental domains of the WHOQOL-Bref questionnaire, a statisticallysignificant difference was observed between the students who did not have and those who had mild or PMDD (p < 0.001). A difference was also found between the students who did not have PMS and those who had mild PMS in the social relationships (p = 0.001) and environmental domains (p = 0.009). Conclusion Mild PMS and PMDD are prevalent among university students on healthrelated courses, and the syndrome can affect the students’ self-assessment of all the domains of quality of life.